Taksonomi Seni Tupping Sebagai Representasi Kehidupan Masyarakat Lampung Selatan - I Wayan Mustika (Mudra Jurnal Seni Budaya, 2022)
Knowing that Performing mask art is getting rare in Indonesia, It is interesting to find out how the art survives and becomes the cultural icon of the regency, in this case, the Performing Tupping in Kesugihan Village, Kalianda, South Lampung. Performing Tupping (Mask) art in Kesugihan Village, Kalianda, South Lampung Regency is a very essential folk art that has been rearranged with character forms from several types. It is interesting to find the history and its taxonomy, from just a village performance until it becomes South Lampung’s cultural icon. This article attempted to describe the taxonomy of Tupping in Kesugihan village, Kalianda, as a cultural icon of South Lampung. The qualitative research was conducted to answer these research questions: 1. How was Tupping’s taxonomy at the beginning and what characteristic did it represent. 2. How is the taxonomy of the modern Tupping and what is behind them. The data were collected through observation, interview, and literary study. Tupping at the beginning was simpler, with only a few characters. They mostly depict ugly figures. Tupping can survive because It has been used since Radin Intan’s reign, especially by her knights for disguising to fight the Dutch. Later in their daily life, Tupping was used for worshipping the spirit and the ancestors and performed as entertainment for the villagers. Taxonomically, There are some types of Tupping with each respective character and what each philosophically means. it also evolves from time to time to catch up with modernization and globalization.